The Impact of Covid-19 Pandemic on Consumer Behavior: J&T Express Courier Services in Malaysia and Indonesia - Liew, Phing Shuin; Liew, Wei Ning; Lim, Cia Shim; Lin, Jenq Yang; Qonitah, Salwa Inka (AIBPM Publisher, 2022)
The Covid-19 pandemic causes people to reduce physical interactions as everyone is encouraged to keep a safe distance to reduce the spreading of the virus. During this pandemic, as cities are locked down, e-commerce has become a trend, and therefore, a delivery company like J&T Express is needed in order to deliver items purchased by customers to their homes. The objective of the study is to find out the impact of the Covid-19 pandemic on consumer behavior towards the intention to use J&T Express services. The data were collected from a survey questionnaire about the consumer behavior in Malaysia and Indonesia towards courier company J&T Express. This study was gathered data from 100 consumers through Google Form. The findings of this research reveal that consumer intention to use the courier services increased during the Covid-19 pandemic.